2012
DOI: 10.1007/s10439-012-0609-1
|View full text |Cite
|
Sign up to set email alerts
|

Could Spatial Heterogeneity in Human Vocal Fold Elastic Properties Improve the Quality of Phonation?

Abstract: The physical mechanisms leading to the acoustic and perceptual qualities of voice are not well understood. This study examines the spatial distribution of biomechanical properties in human vocal folds and explores the consequences of these properties on phonation. Vocal fold lamina propria specimens isolated from nine excised human male larynges were tested in uniaxial tension (six from non-smokers, three from smokers). An optical method was employed to determine the local stretch, from which the elastic modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…The distribution of elastic modulus within the length of the ligament was used as a model for the distribution within the entire VF tissue. Kelleher et al (2012) found this distribution itself changes in cover and ligament layers. Future studies conducted with layered VF tissue models could provide further insights.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The distribution of elastic modulus within the length of the ligament was used as a model for the distribution within the entire VF tissue. Kelleher et al (2012) found this distribution itself changes in cover and ligament layers. Future studies conducted with layered VF tissue models could provide further insights.…”
Section: Discussionmentioning
confidence: 87%
“…Kelleher et al (2012) show that gradients in elastic modulus are smaller in cover and ligament specimens excised from subjects associated with tobacco use than specimens excised from non-smokers. Kelleher et al (2010) show that in vacuo eigenmodes of VF tissue are dependent on gradients in elastic modulus.…”
Section: Introductionmentioning
confidence: 81%
“…Each tissue was mounted in the tensile testing setup in a manner where the specimen's length was near the in situ measurement in order to closely mimic the physiological state. The uniaxial tensile test was conducted for 180 cycles, similar to previous studies on vocal fold elasticity (Kelleher et al, 2011, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…We speculate that the microstructural arrangement likely varies based upon the anterior-posterior location along the vocal ligament as indicated by the heterogeneous elastic response measured in previous studies. 22,30 A more complete analysis should include the fiber dispersion at several locations along the vocal ligament to account for the histological heterogeneity. A recent study has documented the dispersion and density of collagenous fibers of the vocal ligament with more samples and provided a statistical range.…”
Section: Discussionmentioning
confidence: 99%
“…Since vocal fold tissue has been shown to be heterogeneous, it was important that the elastic properties be measured in the same region. 22,30 However, for the constitutive and vibration modeling the elastic properties of the overall tissue (i.e., from the anterior commissure to the vocal process) were used.…”
Section: B Biomechanical Testingmentioning
confidence: 99%